Single women navigating disenfranchised grief in Elizabeth Gaskell's Cranford - Nurulhady, Eta Farmacelia; Juliati, Juliati (Universitas Islam Sultan Agung, 2025)
Written during the Victorian Era, Elizabeth Gaskell’s Cranford (1853) explores social issues related to gender. This study focuses on how the main characters of the novel, the Jenkyns sisters, navigate their loss resulting from being women and single. This qualitative research analyzes the narrative elements of the novel, especially its characters, conflicts and setting, and employs feminist literary criticism to scrutinize the gender relations and inequalities in the novel. Borrowing Kenneth J. Doka’s theory of disenfranchised grief, this study asserts how the community of spinsters and widows in the novel challenges the imposition of women’s identity as wives and mothers. However, while succeeding in managing lives outside of marriage and motherhood, the Jenkyn sisters struggle with grief that cannot be openly acknowledged nor socially validated. Such grief and efforts to conceal lead to psychosomatic symptoms. Remain unmarried, these middle-class women cannot escape social expectations of women in nineteenth-century England that the novel resolves their grief partly by making them a surrogate mother and wife.